MINIMIZING THE DISTRIBUTION OF THE COVID-19 PLAGUE THROUGH ERGONOMIC MASK DESIGN - Meri Andriani; Asnawi; Hanafiah (LPPM dan PM Universitas Samudra, 2021)
The Langsa City Government-issued Circular Number 443.1 / 1066/2020 regarding one of the contents of wearing a mask when outside the home, due to the increasing spread of the Covid-19 outbreak. The Covid-19 outbreak has spread throughout the world, making it a global problem. ASEAN countries that have confirmed positive for contracting Covid-19 are Malaysia, Singapore, Thailand, Vietnam, Cambodia, and the Philippines, Indonesia. Indonesia determined 1,528 positive Covid-19 and 136 cases of death, especially Aceh Province, there were 9 people who tested positive for Covid-19. The recommendation of the Langsa City Government is very hard to be implemented by the residents of Langsa City, it is proven that there are still many Langsa City residents who do not wear masks when outside the house. The aim of this service is to minimize the transmission of the covid-19 outbreak in Langsa City by providing ergonomic masks to the residents of Langsa City. The masks provided are designed so that humans are comfortable wearing them. The Community Service activities started from a field survey, designing ergonomic masks and what Langsa City residents wanted, making masks, then the Service Team and Partners gave Langsa City Residents who did not wear masks while outside the house. Service outputs are ISSN service journals (publish), print media (publish), and products (ergonomic masks). The target that the Service Team hopes for is that residents of Langsa City wear ergonomic masks when they are outside the house and avoid the Covis-19 outbreak by using ergonomic masks.